D DESAIN PENYIMPANAN GABAH KERING PANEN DAN BERAS DENGAN BANGUNAN PASIF ENERGI : Abstrak - Sumarjo, Jojo Sumarjo; siswadi, siswadi (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2024)
Passive design is a way to save energy through the passive use of solar energy, that is, without converting solar energy into electrical energy. the passive design relies more on the ability of engineers how the design of the building itself can